Pembelajaran Luas Permukaan Bangun Ruang Sisi Datar Menggunakan Pendekatan Pendidikan Matematika Realistik Indonesia - Siti Maisyarah; Rully Charitas Indra Prahmana (Universitas Hamzanwadi, 2020)
One of the geometry subjects that has a high level of difficulty and abstractness is the 3D-shape subject (solid geometry), especially the surface area of a polyhedron. Students have difficulty in imagining objects and constructing previously owned knowledge. One approach that uses prior knowledge as a starting point for learning is the Indonesian Realistic Mathematics Education (IRME) approach. This research is a qualitative descriptive study that aims to describe the learning of surface area of polyhedron using the IRME approach to eighth-grade students in SMP Negeri 1 Banguntapan. The subjects of this study were all eighth-grade students of SMP Negeri 1 Banguntapan Yogyakarta. Data collection techniques used were video recording, observation, and interviews. Video recording is conducted to observe student activities during the learning process and compare them with observation and interview sheets. Meanwhile, the test instrument is used as supporting data to see student learning outcomes after learning the surface area of the polyhedron as the whole topic. The results showed that during the learning process, which lasted for two meetings, students could follow well all stages of learning by fulfilled the five characteristics of IRME and getting good results.